2017
DOI: 10.1016/j.ijep.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Early-life status epilepticus induces long-term deficits in anxiety and spatial learning in mice

Abstract: Background One of the most devastating aspects of developmental epilepsy is the long-term impact on behavior. Children with epilepsy show a high co-morbidity with anxiety disorders and autism. Methods To examine whether early-life status epilepticus results in altered anxiety, repetitive behavior, social behavior, and learning and memory, we induced status epilepticus in male C57BL/6 mice on postnatal day (PD) 10. The mice received intraperitoneal injections of either kainic acid (2 mg/kg) or 0.9% no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Disinhibited behaviors observed in the CSE + NS, CSE + PRF 10 mg/kg, and to some extent in the CSE + PRF 20 mg/kg groups subjected to open field test are consistent with a significant increase in the time spent in the open arm, decrease time spent in the close arm, increased number of crossing and the total time spent in the center of the elevated plus-maze. The data from the open field and elevated plus-maze tests are suggestive pieces of evidence that CSE in rats did not induce anxiety-related behavior in contrast to the findings of Inostroza et al 18 and Smith et al 25 but may have damaged the neuronal network of the central nervous system (CNS) with evidence of impairment in the risk assessment and decision-making ability. The exact mechanism through which PRF treatment abrogated these behavioral impairments is still ill-defined.…”
Section: Effects Of Prf Obtained From Vitis Vinifera Seed On the Seru...mentioning
confidence: 70%
See 1 more Smart Citation
“…Disinhibited behaviors observed in the CSE + NS, CSE + PRF 10 mg/kg, and to some extent in the CSE + PRF 20 mg/kg groups subjected to open field test are consistent with a significant increase in the time spent in the open arm, decrease time spent in the close arm, increased number of crossing and the total time spent in the center of the elevated plus-maze. The data from the open field and elevated plus-maze tests are suggestive pieces of evidence that CSE in rats did not induce anxiety-related behavior in contrast to the findings of Inostroza et al 18 and Smith et al 25 but may have damaged the neuronal network of the central nervous system (CNS) with evidence of impairment in the risk assessment and decision-making ability. The exact mechanism through which PRF treatment abrogated these behavioral impairments is still ill-defined.…”
Section: Effects Of Prf Obtained From Vitis Vinifera Seed On the Seru...mentioning
confidence: 70%
“…However, previous studies have shown some of the pharmacological properties exhibited by catechins (one of the major phytoconstituents of proanthocyanidin), most importantly, its good affinities for the benzodiazepine (GABAA) receptor site with resultant anxiolytic, and sedative/ hypnotic actions. 25,26 Social isolation and poor social adaptation among people living with epilepsy have been reportedly linked with fear of embarrassment from seizures, and perceived stigma leading to reluctance to engage in social interaction, with concomitantly low self-esteem. 27 The causes of poor social behavior among people living with epilepsy may be more compared to the submission of Hills, and Nabi et al 28 It would be recalled that the area of the brain responsible for directing appropriate social behavior and interactions with others sits in the prefrontal cortex.…”
Section: Effects Of Prf Obtained From Vitis Vinifera Seed On the Seru...mentioning
confidence: 99%
“…Children diagnosed with epilepsy have a high comorbidity with autism and anxiety [ 24 ]. A study has shown Kainic acid-induced status epilepticus mouse models have impaired spatial and anxiety behavior [ 25 ]. We hypothesize that EPCR R84A/R84A and PAR1 R46Q/R46Q would exhibit more anxiety-like behavior than our control group under normal conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The rats were placed in the apparatus and escape latency was monitored. The apparatus consists of a large circular pool including a wooden material below (19) .…”
Section: Water Maze Testmentioning
confidence: 99%